The Impact of Health Literacy on Palliative Care Outcomes. Issue 6 (December 2016) - Christensen, Deborah
Abstract : Limited health literacy is a recognized health problem often leading to poorer health outcomes. Health care professionals, including nurses, are responsible for delivering health information in a clear and understandable way. Yet nurses may overestimate patients' health literacy and miss opportunities to help patients understand and then incorporate medical information. Health outcomes may improve when nurses recognize potential barriers to health literacy and use evidence-based interventions. A review of current research regarding health literacy is provided to assist nurses with communication strategies in their delivery of palliative care.